2021
DOI: 10.3389/fimmu.2020.603029
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Cationic Autoantigen Mimics Glatiramer Acetate Persistence at the Site of Injection and Is Efficacious Against Experimental Autoimmune Encephalomyelitis

Abstract: A synthetic peptide, K-PLP, consisting of 11-unit poly-lysine (K11) linked via polyethylene glycol (PEG) to proteolipid protein epitope (PLP) was synthesized, characterized, and evaluated for efficacy in ameliorating experimental autoimmune encephalomyelitis (EAE) induced by PLP. K-PLP was designed to mimic the cationic nature of the relapsing-remitting multiple sclerosis treatment, glatiramer acetate (GA). With a pI of ~10, GA is able to form visible aggregates at the site of injection via electrostatic inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In our work, we aimed to establish a novel approach for the precise determination of GA and its amino acids: l-alanine, l-lysine, l-tyrosine, and l-glutamic acid. The isoelectric point (pI) of GA was estimated to be 10 [22], while the pIs of the amino acids are as follows: l-glutamic acid 3.22, l-tyrosine 5.66, l-alanine 6.01, and l-lysine 9.74 [3]. After conducting preliminary tests in the pH range of 2-10, it was found that the use of an acidic buffer is advantageous for the following analysis.…”
Section: Methods Developmentmentioning
confidence: 99%
“…In our work, we aimed to establish a novel approach for the precise determination of GA and its amino acids: l-alanine, l-lysine, l-tyrosine, and l-glutamic acid. The isoelectric point (pI) of GA was estimated to be 10 [22], while the pIs of the amino acids are as follows: l-glutamic acid 3.22, l-tyrosine 5.66, l-alanine 6.01, and l-lysine 9.74 [3]. After conducting preliminary tests in the pH range of 2-10, it was found that the use of an acidic buffer is advantageous for the following analysis.…”
Section: Methods Developmentmentioning
confidence: 99%
“…[103] Various preclinical studies using biomaterials focus on S.C. delivery. [99][100][101][102][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120] These therapies combine antigen with immunomodulatory cues (i.e., cytokines, toll-like receptor antagonists, immunosuppressants, etc.) through loading or coupling with NPs and MPs to enable combinatory presentation to relevant immune cells.…”
Section: Polymeric Biomaterials Delivered Subcutaneously Take Advanta...mentioning
confidence: 99%